Oceanographic Data of the 36th Japanese Antarctic Research Expedition from November 1994 to March 1995 - ヨリタカ, ヒロユキ; ナミキ, マサハル; YORITAKA, Hiroyuki; NAMIKI, Masaharu (National Institute of Polar Research, 1999)
P(論文) The results of oceanographic observations on board the icebreaker "Shirase" and tidal observations at Syowa Station, Antarctica, are presented in this report. The oceanographic observations were carried out by the summer party of the 36th Japanese Antarctic Research Expedition (JARE-36) during the austral summer of 1994/1995. The tidal observations were carried out by the winter party of JARE-35 from February 1994 to January 1995. departmental bulletin paper